2020
DOI: 10.3389/fcell.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 Inflammasome in Radiation-Induced Cardiovascular Injury

Abstract: The increasing risk of long-term adverse effects from radiotherapy on the cardiovascular structure is receiving increasing attention. However, the mechanisms underlying this increased risk remain poorly understood. Recently, the nucleotide-binding domain and leucine-rich-repeat-containing family pyrin 3 (NLRP3) inflammasome was suggested to play a critical role in radiation-induced cardiovascular injury. However, the relationship between ionizing radiation and the NLRP3 inflammasome in acute and chronic inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 231 publications
(195 reference statements)
0
14
0
Order By: Relevance
“…Upregulated NLRP3 promotes caspase-1-mediated inflammatory cascade and induces the expression of downstream proinflammatory factors, such as IL-1 β , IL-6, and TNF- α [ 24 , 36 ]. It has been reported that NLRP3 inflammasome-mediated pyroptosis is involved in exacerbating radiation-induced intestinal injury and radiation-induced cardiovascular injury [ 37 , 38 ]. Here, we demonstrated that NLRP3, caspase-1, and IL-1 β were activated in a radiation-induced mouse model of intestinal injury and cell culture model.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated NLRP3 promotes caspase-1-mediated inflammatory cascade and induces the expression of downstream proinflammatory factors, such as IL-1 β , IL-6, and TNF- α [ 24 , 36 ]. It has been reported that NLRP3 inflammasome-mediated pyroptosis is involved in exacerbating radiation-induced intestinal injury and radiation-induced cardiovascular injury [ 37 , 38 ]. Here, we demonstrated that NLRP3, caspase-1, and IL-1 β were activated in a radiation-induced mouse model of intestinal injury and cell culture model.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in external conditions can also impact the adaptation of HSPCs. For example, BM cells and hematopoiesis can be severely affected by high-dose radiotherapy [ 47 , 48 , 49 ]. The process involves a series of cellular and molecular changes, such as the depletion of hematopoietic cells, proinflammatory cytokine and chemokine release, activation and destruction of peripheral immune cells, and DNA damage [ 49 , 50 ].…”
Section: Relationship Between Inflammasomes and Hematopoiesismentioning
confidence: 99%
“…2 ). Necrotic cells release factors like endogenous mitochondrial damage-associated molecular patterns (DAMPs), including high mobility group box 1 (HMGB1), ATP, and IL-1α produced by stressed cells to evoke an inflammatory response [ 78 , 79 ]. These signals are sensed by the nucleotide-binding domain and leucine-rich-repeat-containing family pyrin 3 (NLRP3), a core protein of the inflammasome.…”
Section: Pathomechanisms Of Rihdmentioning
confidence: 99%
“…NLRP3 activates and releases the pro-inflammatory cytokine IL-1β and IL-18. RT may activate NLRP3 inflammasome via multiple other mechanisms, including increased oxidative/nitrosative/nitrative stress, calcium ion influx, and potassium ion efflux [ 78 , 79 ]. NLRP3 inflammasome was suggested to play a critical role in the development of RIHD via its complex relationship with cell death and inflammatory processes [ 78 , 79 ].…”
Section: Pathomechanisms Of Rihdmentioning
confidence: 99%